CAESAREAN SECTION IN A LARGE WHITE YORKSHIRE GILT - Selvaraju, M; Ravikumar, K; Senthilkumar, S; Palanisamy, M; Prabaharan, V; Ravi, R; Chandrahasan, C (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The major indications for caesarean section in sows are irreducible vaginal prolapse, foeto-pelvic disproportion including foetal emphysema, non-dilatation of the cervix and uterine inertia (Arthur et al.,1996). Caesarean section is easier and safer than other obstetrical operations in sow, bitch and cat (Roberts, 1971). The present study records a case of dystocia due to uterine inertia and successful caesarean operation under local infiltration anaesthesia in Large White Yorkshire gilt.
Keywords: CAESAREAN; SECTION; YORKSHIRE